REALISASI NILAI-NILAI PANCASILA BAGI PEMELUK ISLAM, KRISTEN DAN HINDU DI DESA CANDI-KLATEN - Muhammad Alwi Alwi HS (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2021)
This article examines the realization of Pancasila values by focusing on the life of Candi village community, Klaten, especially regarding the relationship among Muslims, Christians, and Hindus. The primary data in this article were obtained from the field, in the form of interviews with the community and village level, observations, and documentation. Meanwhile, secondary data in this article as much as possible is obtained from articles and books related to the theme. The results of this article show that the relationship among the three religious adherents shows the realization of Pancasila values. This realization aims to overcome and foster religious diversity in the village, by implementing and prioritizing the interests of the State or the structural rules of government (village apparatus) that have been agreed and enforced, among at the village head, RT, and RW levels. In addition, the involvement of religious leaders and youth organizations also contributes to supporting the prioritization of the interests of the State or the government structure.